Play, Learn, and Grow: Enhancing Character Education in Elementary Schools through Traditional Games - A. Ardiansyah; Hendriana Sri Rejeki; Abdul Gafur Marzuki; Mohammad Djamil M. Nur; Ulfah Ulfah (Institut Agama Islam Negeri Imam Bonjol Padang, 2025)
Traditional games serve as a means of playing and, at the same time, a means of communication. A traditional game is one that has character values because it can build them. The object of this research is elementary school children who play traditional games. This research is qualitative research. Research data were collected through observation, interviews, and documentation. The validity of the research data was retested using extended participation, observation, persistence, and triangulation. The results signaled that traditional games can be used as a vehicle for playing because they have benefits for children; not only that, they are also a means of communication and can build character in elementary school children.